Quantitative Evidence on Transparency in Regional Trade Agreements - Lejárraga, Iza (OECD Trade Policy Papers, 2013)
What influences the adoption of transparency obligations in trade agreements, and what are its effects? This paper uses a new dataset on transparency provisions in over a hundred regional trade agreements (RTAs) to provide empirical evidence of the political economy determinants of international transparency commitments, as well as the trade impact of negotiating such transparency provisions in RTAs. The study finds that RTAs with deeper mechanisms for enhancing transparency appear to be more strongly trade-promoting than those with shallower commitments on transparency. Concretely, each additional transparency commitment negotiated in an RTA is associated with an increase in bilateral trade flows of more than one percent. Considering that comprehensive RTAs typically contain a dozen of such commitments, countries that opt for a comprehensive transparency agenda can expect to gain substantial increases in intra-regional trade. Moreover, the findings suggest that the readiness of trading partners to adhere to transparency norms is influenced by the quality of home institutions, which is consistent with a view that strengthening governance and regulatory capacities can contribute to a broader diffusion of transparency practices in international trade. Overall, the results of the analysis suggest that transparency should remain an important element of the trade agenda, both at the regional and multilateral levels